2015
DOI: 10.1186/s13054-015-0882-0
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mechanical ventilation–induced neuroinflammation affects postoperative memory dysfunction in surgical mice

Abstract: IntroductionPatients undergoing surgery frequently develop neuropsychological disturbances, including cognitive decline or memory impairment, and routine clinical procedures such as mechanical ventilation (MV) may affect acute-phase brain outcome. We aimed to investigate the effect of the prolonged MV on postoperative memory dysfunction in surgical mice.MethodsMale C57BL/6 mice were randomly divided into the following three groups: (1) The control group (group C) comprised anesthetized, unventilated animals; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 31 publications
(31 reference statements)
0
58
1
Order By: Relevance
“…Relevance of MV-induced alveolar stretching in brain damage is witnessed by production of cerebral beta-amyloid and Alzheimer’s disease-like brain degeneration (cerebral amyloid β peptide accumulation, neuroinflammation, and blood-brain barrier dysfunction) even after relatively “short-term MV” (after 4 h MV in mice)—as reported in a recent study published in Critical Care [8]. The PaO 2 /PaCO 2 abnormalities—including hypo and hyper O 2 and/or CO 2 that often represent the indication to establish MV and can persist during MV—might contribute to promote neuronal death, cerebral oxidative stress, and changes in brain blood flow that worsen brain damage [10, 11]. Increased systemic inflammatory mediators produced by the lungs during MV (“biotrauma”) have been detected in several preclinical studies and include TNF alpha, IL6, IL10, IL1 beta, MCP1, and MIP2, which have a proven neuroinflammatory role [4, 5, 7].…”
Section: Mv-induced Brain Damage: Mechanisms Localization and Timingmentioning
confidence: 87%
“…Relevance of MV-induced alveolar stretching in brain damage is witnessed by production of cerebral beta-amyloid and Alzheimer’s disease-like brain degeneration (cerebral amyloid β peptide accumulation, neuroinflammation, and blood-brain barrier dysfunction) even after relatively “short-term MV” (after 4 h MV in mice)—as reported in a recent study published in Critical Care [8]. The PaO 2 /PaCO 2 abnormalities—including hypo and hyper O 2 and/or CO 2 that often represent the indication to establish MV and can persist during MV—might contribute to promote neuronal death, cerebral oxidative stress, and changes in brain blood flow that worsen brain damage [10, 11]. Increased systemic inflammatory mediators produced by the lungs during MV (“biotrauma”) have been detected in several preclinical studies and include TNF alpha, IL6, IL10, IL1 beta, MCP1, and MIP2, which have a proven neuroinflammatory role [4, 5, 7].…”
Section: Mv-induced Brain Damage: Mechanisms Localization and Timingmentioning
confidence: 87%
“…Quílez et al described how MV induced differential c-fos expression in several areas in the brain, depending on the ventilatory pattern, tidal volume (VT) and level of PEEP, thus supporting the hypothesis that an iatrogenic effect of MV may affect the brain (14,18). Chen et al found that prolonged MV (6 h) in mice induced cognitive decline and increased activation of microgliosis and apoptotic cascades after surgery, thus indicating the detrimental effects of prolonged MV in the brain (19). González-López et al identified a novel mechanism driven via vagal and dopaminergic pathways that triggers hippocampal apoptosis in response to lung stretch in mice undergoing MV (20).…”
Section: And the Brainmentioning
confidence: 91%
“…In addition, during cardiac surgery, extracorporeal circulation, temperature management, anaesthetic dose, tissue ischaemia-reperfusion, regulation of cerebral blood flow, and oxygen saturation may all cause neuroinflammation and cognitive impairment [ 145 ]. Intraoperative and postoperative long-term mechanical ventilation increase the expression of peripheral and hippocampal inflammatory cells, activation of the apoptotic cascade, and reactive hyperplasia of the microglia by activating the vagus nerve and triggering type 2 dopamine receptors, which further aggravates cognitive decline [ 146 , 147 ].…”
Section: Methodsmentioning
confidence: 99%